Electrical discharge machining of siliconized silicon carbide using copper electrode - Sarabi, Arash Mazaheri (2014)
Silicon Carbide is the semiconductor material that becoming popular because of its special characteristic. But, its application is limited due to processing difficulty. Advance machining process is found to be the best and economic way to fabricate this material. However, certain parameters need to be controlled for controlling the accuracy and efficiency of the process. This study presents analysis of some parameters in EDM machining of this material. The Silicon Carbide used for the study is limited to Reaction Bonded Silicon Carbide (SiSiC). Several effects of parameter setting such as on-time (ON), discharge current (I), off-time (OFF) and polarity (Pol) on material removal rate (MRR), surface roughness (Ra), tool wear ratio (TWR), and surface roughness (Ra) is studied. The analysis was done using Design Expert Software by implementing design of experiment method. From this analysis, the significant effect(s) is determined. From that, the mathematical models that consist of only significant effect(s) are established. In order to ensure validity of the model, conformation run is done with three different parameters setup. Finally, the optimum setting to get maximum material removal rate, minimum tool wear ratio and minimum surface roughness is determined. Overall, the results show that the effects of pulse on-time and Polarity are dominant for all responses established